HIP-storytelling: hand interactive projection for storytelling - Melo, Narciso (2011)
We have created an interactive storytelling system for public spaces that is collaborative, easy and entertaining to use, and allows for a natural inte-raction. The system consists of a table, a ceiling mounted projector that projects onto the table, and a 3D camera for tracking hands and for object recognition. The main feature of the system is the projection on top of the palm of the hand of the users; thus, the hand becomes also a viewing surface. This allows for very natural gestural interaction, such as holding and passing objects between users. For example, in the course of narrative, users can hand over a story cha-racter or object to each other. We also employ projection based augmented real-ity to animate real objects on the table. Apart from entertainment, the system shall be employed for concrete educational interactive storytelling applications in public spaces.